Bioresorbable vascular scaffold versus metallic drug-eluting stent in patients at high risk of restenosis: the COMPARE- ABSORB randomised clinical trial - Smits, Pieter C.; Chang, Chun Chin; Chevalier, Bernard; West, Nick E. J.; Gori, Tommaso; Barbato, Emanuele; Tarantini, Giuseppe; Kocka, Viktor; Achenbach, Stephan; Dudek, Dariusz; Escaned, Javier; Wlodarczak, Adrian; et al. (EuroIntervention, 2020)
Aims: The aim of this study was to investigate clinical outcomes of patients at high risk of restenosis after implantation of a bioresorbable vascular scaffold (BVS).
CRIS-Team WoS Importer:2020-11-13